Access to Counsel: Psychological Science Can Improve the Promise of Civil Rights Enforcement. (October 2014) - Kaiser, Cheryl R.; Quintanilla, Victor D.
Employment discrimination claimants in general, and racial minority claimants in particular, disproportionately lack access to legal counsel. When employment discrimination claimants lack counsel, they typically abandon their claims, or if they pursue their claims, they do so pro se (without counsel), a strategy that is seldom successful in court. Access to counsel is, hence, a decisive component in whether employment discrimination victims realize the potential of civil rights enforcement. Psychological science analyzes access to counsel by identifying psychological barriers—such as threatened social identity, mistrust in legal authorities, and fear of repercussions—that prevent employment discrimination victims from pursuing counsel. The analysis also identifies how cultural beliefs and practices concerning justice—such as meritocracy beliefs, perceived post-racialism, and organizational diversity initiatives—shape how judges, jurors, and lay people think about discrimination. Furthermore, counsels' perceptions of other's beliefs about discrimination shape their assessed likelihood of prevailing. These psychological barriers intersect with structural barriers to shape counsels' evaluation of each case's likely financial viability, which can prevent counsel from accepting cases that they otherwise deem meritorious. Policy can help those who experience employment discrimination obtain legal representation and meaningful redress for civil rights violations.